The Existence of Google Classroom in Online Speaking Skills Learning by Papuan EFL Students at the University Level - Rahmawansyah Sahib; Ade Yamin; Tegar Aulia; Kurnia Putri Ayu (STAI Hubbulwathan Duri, 2022)
This study will offer and fill the gap of prior research in the context of acquiring speaking skills using Google Classroom as a Learning Management System by EFL students in Papua during Covid-19. This study aimed to explore the processes and students' strategies to face online learning speaking skills using Google Classroom during the covid-19 pandemic. This study applied a qualitative descriptive design involving participants from students of Tadris English who took speaking subjects through Google Classroom. Furthermore, data were collected through offline interviews and online observations. Then, analyzed qualitatively based on the theory of John W Creswell. The results showed that the process of acquiring speaking abilities using Google Classroom proves to be difficult for students who want to improve their English speaking skills. Because they have recently introduced Google Classroom in the learning process and learning is taking place for the first time in a fully online learning setting. As a result, students are more inclined to prioritize studying Google Classroom above mastering English competency itself. More research is needed to investigate Google Classroom from the lecturer's point of view in the context of teaching English in Papua in order to provide more full references and information about the usage of Google Classroom in English classrooms in Papua.